'First tonight, the contentious new code telling nurses to say, 'sorry for being white': Mental health nurses' beliefs about their Code of Conduct and cultural safety for Aboriginal and Torres Strait Islander Peoples. (2nd August 2021) - Molloy, Luke; Beckett, Paul; Chidarikire, Sherphard; Scott, Matthew P.; Guha, Monica D.; Tran Merrick, Tammy; Patton, Declan
Abstract: The Nursing and Midwifery Board of Australia's Code of Conduct for Nurses sets out the professional behaviour and conduct expectations for nurses in all practice settings. The publication of a revised version in 2018, which included expectations related to culturally safe and respectful practice and Aboriginal and Torres Strait Islander Peoples' health, caused reverberations beyond the profession of nursing. A controversy that the changes required nurses to verbally apologize for being white before their interactions with Aboriginal and Torres Strait Islander people gained the attention of the mainstream media. This interpretation, which came from outside nursing, was disputed by the Board. Challenged by these events, the authors were interested in understanding the actual impacts of the changes from the perspectives of nurses in practice. This research, carried out nearly three years after publication, has focused specifically on the speciality of mental health nurses in this context. The objective of this research was to undertake a social analysis focused on the impact that changes in the Code have had on the culture of mental health nursing utilizing a qualitative methodology. Eight mental health nurses were interviewed. The research found that there was little evidence of any impact on mental health nursing practice. Many of the participants were unaware of the amendments to the Code, whilst those nurses who were aware did not perceive that it had led to any real change within mental health nursing or service delivery.